Immuno-physiological response of Litopenaeus vannamei in oil palm kernel meal based biofloc systems - SYAMALA, KARTHIREDDY; LAKRA, W S; CHADHA, N K; SAHU, N P; PRASAD, K PANI; MURALIDHAR, A P (The Indian Journal of Animal Sciences, 2018)
A 45-day experiment was conducted to assess the immuno-physiological response of Litopenaeus vannamei in oil palm kernel meal based biofloc systems. L. vannamei of average weight (0.82±0.02 g) were stocked in tanks at a stocking density of 300 PL/m3. Biofloc-based treatment obtained significantly better growth performance at the end of the experimental period. The stress parameters like SOD, CAT, LDH and GST were considerably lower in biofloc-based treatment as compared to the control. The oil palm based biofloc system showed lower AST and ALT values than the clear water control. The shrimp from biofloc treatment possessed significantly higher immune status as compared to control regarding the prophenol oxidase (proPO) activity. Biofloc treatment showed higher relative survival percentages than control. It indicates that oil palm kernel meal can be used as a potential carbon source for biofloc based shrimp culture.